Gender, informal institutions and political recruitment : explaining male dominance in parliamentary representation - Bjarnegard, E (Politiska partier och politisk representation ur ett genusperspektiv. Betydelsen av byråkratisering i kandidatnomineringsprocessen, 2013)
01 02 Parliaments around the world are still overwhelmingly populated by men, yet studies of male dominance are much rarer than are studies of female under-representation. In this book, men in politics are the subjects of a gendered analysis. How do men manage to hold on to positions of power despite societal trends in the opposite direction? And why do men seek to cooperate mainly with other men? Elin Bjarnegård studies how male networks are maintained and expanded and seeks to improve our understanding of the rationale underlying male dominance in politics. The findings build on results both from statistical analyses of parliamentary composition worldwide and from extensive field work in Thailand. A new concept, homosocial capital, is coined and developed to help us understand the persistence of male political dominance. 16 02 The readers of the book on Gender, Politics and Institutions by Krook and Mackay (2011, Palgrave Macmillan) should be interested in this book, since it speaks with the same institutional language, but delves deeper into how institutions actually work in specifically gendered ways. It adds a gendered perspective to the growing neo-institutionalist literature on informal institutions, exemplified in Informal Institutions & Democracy by Helmke and Levitsky (2006, John Hopkins University Press). Readers of The Handbook of Studies on Men and Masculinity, edited by Kimmel, Hearn and Connell (2005, Sage Publications) have probably noted the absence of political studies. 13 02 ELIN BJARNEGÅRD is Assistant Professor at the Department of Government, Uppsala University, Sweden. Her research interests include Informal institutions, Gender issues and Thai Politics. 02 02 In this book, men in politics are the subjects of a gendered analysis with Elin Bjarnegård exploring how male networks are maintained and expanded, seeking to improve our understanding of the rationale underlying male dominance in politics. The role of informal institutions in unpredictable political settings are explored. 08 02 'This fascinating new book broadens our horizons in a number of ways. It firstly challenges us to think about male dominance rather than female under-representation in politics, using a range of methods and data derived from detailed empirical research. Second it develops a concept of homosocial capital and uses it in novel ways to to give us significant new insights into the gendered impact of clientelism and informal institutions on candidate selection. This book is an important addition to the gender and politics scholarship and deserves to be widely read.'   Georgina Waylen, Professor of Politics, University of Manchester, UK      'The relation between gender equality, corruption and clientelism in democratic governance is as important as it is fascinating. In this theoretically sophisticated and empirically impressive work, Elin Bjarnegård presents a novel understanding not only for why male dominance in democratic politics can be reproduced through clientelistic network, but also how the specific mechanisms between informal power and democratic representation operate'   Bo Rothstein, August Röhss Chair in Political Science, Göteborg University, Sweden. 'Throwing fresh light on the age-old puzzle of male dominance in elected office, this book provide a new theoretical framework by developing the concept of homosocial capital, often known as 'old boys networks', which are particularly useful for men seeking to get ahead in countries with clientalistic politics. Drawing upon evidence from global trends, the study also utilizes insights drawn from in-depth case-study of Thai politics. The clear, informative and illuminating study gives new insights into the challenges which need to be overcome to achieve gender equality in elected office'   Pippa Norris, Mcquire Lecturer in Comparative Politics John F. Kennedy School of Government, Harvard University, USA and ARC Laureate Fellow and Professor of Government and International Relations at the University of Sydney, Australia 31 02 This book explains male dominance in politics by focusing on the role of informal institutions in political recruitment 04 02 Upholding Male Parliamentary Dominance Revisiting Patterns Of Gendered Representation Structure Of The Book Studying Men And Masculinities In Politics Constructing Homosocial Capital Clientelism And Unpredictability Clientelism As A Likely Producer Of Homosocial Capital Clientelism And Male Dominance Institutional Enablers Of Clientelism Combining Methods The Quantitative Approach The Qualitative Approach The Representation Of Men Worldwide Capturing Clientelism – Measuring The Immeasurable? The Models, Data And Operationalizations Clientelism And Male Parliamentary Dominance Results And Implications Of The Quantitative Study Situating The Thai Case The Thai Gender Paradox Democratic Instability In Thailand Informal Influence Assessing The Clientelist Political Logic The Thai Case: Clientelism And Male Dominance Candidate Selection In Thai Political Parties The Importance Of Candidate Selection The Rules Of The Game Who Decides? Summarizing Thai Candidate Selection Clientelist Networks And Homosocial Capital The Role And Function Of Clientelist Networks Network Maintenance And Homosocial Capital Theorizing Homosocial Capital The Gendered Consequences Of Clientelist Competition The Added Value Of Homosocial Capital Concluding Remarks A Summary Of The Findings The Contributions Of The Book Interviews References Notes 19 02 The book addresses an old topic in a new way: gender and politics here means male dominance in politics. The book explains how men have managed to hold on to political power rather than why women are stil largely absent The book combines a statistical analysis of over 400 elections worldwide, with an indepth analysis of localized political networks in Thailand (based on 150 interviews). This combination of methods in one and same book, addressing one and the same research question, is very rare The book launches a new concept: homosocial capital. This concept has a wide applicability across many fields and draws from literature on social capital and homosociality. It is used to explain and rationalize the tendency of men to interact with other men in order to preserve power It is one of few works on Thai politics that focuses on gender. It also ties gender inequalities together with the political turbulence in Thai politics The book takes a new look at democratization and shows that semi-democracies often are weak, both in terms of institutional strengths and gender equality